FACTORS ASSOCIATED WITH DELAYS IN BPJS HEALTH E-CLAIM SUBMISSION AT A GOVERNMENT HOSPITAL IN SRAGEN REGENCY - Sri Nurul Kuraini; Anggi Napida Anggraini; Nella Tri Surya (LPPM STIKES HUSADA JOMBANG, 2026)
Background: Delays in BPJS Health e-claim submission remain an administrative challenge that may affect hospital cash flow and operational sustainability. The complexity of claim processes requires effective management of human resources, medical documentation, information systems, regulations, and organizational support. Objectives: This study aimed to identify factors associated with delays in BPJS Health e-claim submission at a government hospital in Sragen Regency. Methods: This quantitative study used a cross-sectional design involving 19 officers directly involved in the BPJS e-claim process. Total sampling was applied. Data were collected using Likert-scale questionnaires and claim document observations. Variables included human resource quality, completeness of medical documents, information system quality, BPJS regulations, and hospital management support. Data were analyzed using descriptive analysis and Fisher’s Exact Test due to the small sample size. Results: Most respondents were aged 31–40 years (52.6%), female (68.4%), had a bachelor’s degree (52.6%), and had long work experience (42.1%). Fisher’s Exact Test showed significant associations between claim delays and human resource quality (p=0.000), completeness of medical documents (p=0.001), information system quality (p=0.045), and hospital management support (p=0.018). No significant association was found between BPJS regulations and claim delays (p=0.650). The most prominent factors related to claim delays were human resource quality and medical document completeness. Conclusion: Delays in BPJS Health e-claim submission were associated with human resources, medical document completeness, information system quality, and hospital management support. Strengthening staff competency, improving real-time medical record completeness monitoring, and optimizing BPJS e-claim system integration are recommended to improve claim submission efficiency and hospital financial management.